Down-Regulation Ovulation-Induction Leads to Favorable Outcomes in a Single Frozen-Thawed Blastocyst Transfer RCT - Chao, Shi-Bin; Wang, Yan-Hong; Li, Jian-Chun; Cao, Wen-Ting; Zhou, Yun; Sun, Qing-Yuan (Frontiers in Endocrinology, 2022)
Objective: Elective single embryo transfer (eSET) has been increasingly advocated to achieve the goal of delivering a single healthy baby. A novel endometrial preparation approach down-regulation ovulation-induction (DROI) proposed by our team was demonstrated in an RCT that DROI could significantly improve the reproductive outcome compared with modified natural cycle. We aimed to evaluate whether DROI improved clinic pregnancy rate in this single frozen-thawed blastocyst transfer RCT compared with hormone replace treatment (HRT). Method: Eligible participants were recruited and randomized into one of two endometrial preparation regimens: DROI or HRT between March 15, 2019 and March 12, 2021. The primary outcome was clinical pregnancy rate (CPR). The secondary endpoints included ongoing pregnancy rate (OPR), biochemical miscarriage and first trimester pregnancy loss. This trial is registered at the Chinese Clinical Trial Registry, number ChiCTR2000039804. Result(s): A total of 330 women were randomized in a 1:1ratio between two groups and 289 women received embryo transfer and completed the study (142 DROI; 147HRT).Pregnancy outcomes were significantly different between the two groups. The CPR and OPR in the DROI group were significantly higher than those of the HRT group (64.08% versus 46.94%, P＜0.01; 56.34% versus 38.78%,P＜0.01). The biochemical miscarriage and first trimester pregnancy loss were comparable between the two groups. Conclusion(s): The findings of this RCT support the suggestion that the DROI might be a more efficient and promising alternative endometrial preparation approach for FET. Moreover, DROI could play a critical role in promoting uptake of single embryo transfer strategies in FET.